Istikshāf al-Takfīr wa Uṣūluhu wa Istikhdāmātuhu: Muqāranat Kufr al-Ta’wīl bayna al-Ashā‘irah wa al-Salafiyyah al-Wahhābiyyah - Wibowo, Waskito; Fadillah, Nur Aisyah; Madi, Ahmed A. A.; Mabrook, Bassam Hadi Mohammed (Al-Zahra: Journal for Islamic and Arabic Studies, 2024)
This article seeks to analyze and focus on institutional Salafism, also referred to as Wahhabism. The term "Salafism" was not associated with Wahhabi doctrine until the 1970s. It is said that in the early 20th century, Wahhabis began calling themselves Salafis. In contemporary academic discussions, the terms "Salafism" and "Wahhabism" are sometimes used interchangeably. Using a library-based research method, this article concludes that not all Salafis hastily declare others as infidels, including the Wahhabis. They distinguish between apparent issues and hidden issues in the matter of individual takfir (excommunication). They hold that anyone who falls into acts of apparent polytheism, after the evidence from the Quran and Sunnah has been presented to them, is individually excommunicated. However, in hidden matters, a person is not declared an infidel unless their doubts have been entirely dispelled.